A proportional appraisal of smile perception by laypersons, dental professionals, and a smile designing software: An in vivo study - Trushakumari Bhavanbhai Patel; Somilkumar Mathur; Snehal R Upadhyay; Takshil Devendra Shah (The Journal of Indian Prosthodontic Society, 2021)
Aim: To equivalence the perception of smile among laypersons, dental professionals and a commercially available popular smile designing software. Settings and Design: In vivo – comparative study. Materials and Methods: A total of 72 participants within age range of 18-30 years were randomly selected with a natural permanent dentition. All the subjects underwent extra oral and intra oral photographic evaluation as per the American Academy of Cosmetic Dentistry (AACD) guidelines. A total of 11 evaluators were selected for the study and were divided into four groups. The evaluation procedure comprised of assessment of patients' natural smile by laypersons, dental professionals and a smile designing software. A questionnaire was prepared for recording the responses which included a five-point Likert scale. Statistical Analysis Used: Data was statistically analysed using SPSS version 23. Frequencies and chi square test were done for intergroup comparison. Results: There was a statistically significant difference present in comparison across P < 0.05 all the groups. Conclusions: There was significant difference in the perception of smile among evaluators and a smile designing software. Smile designing software prefers to modify the smile as per in built criteria and is more inclined towards creating an ideal smile.